2021
DOI: 10.1002/cam4.3953
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab combined with paclitaxel or paclitaxel alone for patients with recurrent or metastatic head and neck squamous cell carcinoma progressing after EXTREME

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“… 36 , 37 In addition, rechallenge of cetuximab with chemotherapy for patients with R/M-HNSCC showed better ORR than those who received chemotherapy without cetuximab (16.4%-33.3% versus 6.2%, respectively). 19 , 38 Consistent with these previous reports, rechallenge with cetuximab after PD-1 inhibitor appeared to yield a meaningful response in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 36 , 37 In addition, rechallenge of cetuximab with chemotherapy for patients with R/M-HNSCC showed better ORR than those who received chemotherapy without cetuximab (16.4%-33.3% versus 6.2%, respectively). 19 , 38 Consistent with these previous reports, rechallenge with cetuximab after PD-1 inhibitor appeared to yield a meaningful response in our study.…”
Section: Discussionsupporting
confidence: 92%
“… 16 , 17 , 18 By contrast, in a retrospective study, the efficacy of paclitaxel with or without cetuximab for platinum-refractory R/M-HNSCC was modest as compared with the first-line setting, with an ORR of 6.2%-30%, a median PFS of 2.5-4.2 months, and a median OS of 4.2-6.9 months. 2 , 19 , 20 Recently, retrospective studies have suggested that chemotherapy after immune checkpoint inhibitors showed better efficacy than a historical control of chemotherapy in the platinum-refractory setting. The ORR, median PFS, and median OS in such conditions were 30%-54%, 2.1-4.2 months, and 6.9-9.8 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…ORR was 30%, with 4% complete response (CR), and DCR was 57%. Nonetheless, the ORR is three to five times higher than ORR reported in second line for R/M HNSCC in a heavily treated population [7][8][9][10][11][12][13]16]. The combination of cetuximab þ taxane AE platinum was associated with higher ORR than other CT regimens (53% vs. 25%, P ¼ 0.024).…”
Section: Clinical Datamentioning
confidence: 85%
“…After first line, single agent with Methotrexate, Docetaxel, or EGFR inhibitor alone, were options with ORR ranging between 5% and 15%, median progression free survival (mPFS) between 2 and 6 months and median overall survival (mOS) between 6 and 7 months [7][8][9][10][11]. Noteworthy, the combination of Cetuximab with taxanes is associated with better outcomes than taxanes used alone [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hitt et al ( 32 ), in a phase II non-randomized trial demonstrated an ORR of 54% and a median PFS and OS of 4.2 months and 8.1 months, respectively, in patients treated with first-line wkPCx. In the second-line setting, Chevalier et al ( 33 ), reported an ORR of 16.4% and a 5.5-month median OS with wkPCx. In the Keynote-B10 study mentioned before, there were no differences between using three-weekly paclitaxel (175 mg/m 2 d1) and weekly paclitaxel (100 mg/m 2 d1,8), suggesting that weekly paclitaxel may be similar in terms of efficacy with a potentially more favourable toxicity profile ( 11 ).…”
Section: Discussionmentioning
confidence: 99%